Increasing Numbers of Children Aged 5-19 Years with Memory Problems in Sweden and Norway - Nilsson, Mona; Hardell, Lennart (Archives of Clinical and Biomedical Research, 2025)
Previous studies have reported negative impact on memory and cognitive functions in humans and animals from exposure to microwaves, also called radiofrequency (RF) radiation, emitted from wireless technology. In this register based study, data from the Norwegian Syndromic Surveillance System (NorSySS) on memory impairment (ICPC-2 code P20) in children aged 5-19 years during 2006 to 2024 were obtained. Similarly, from The Swedish National Board of Health and Welfare’s national patient register on number of patients aged 5-19 years in specialized open care, diagnosed during 2001 and 2024 with codes related to memory problems or disturbances (R41.3, R41.8 or F06.7), were assessed. In Norway the consultations increased from 179.51 in 2006 to 1,522.40 per 100,000 inhabitants in 2024, representing an 8.5 times increase. The increase was especially pronounced in recent years. A similar trend was observed in Sweden with increasing yearly number of patients with mild cognitive impairment diagnosis (R41.8), particularly from 2010 with 0.86 patients to 51.531 patients per 100,000 inhabitants in 2024, thus an increase of nearly 60 times during that time period. During that time period children’s exposure to microwave RF radiation has increased substantially. We postulate that this can be a causative factor for these increasing trends in consultations for memory problems in Norway and diagnosis of cognitive impairment, including memory problems, in Sweden.